ІНСТИТУЦІЇ В УМОВАХ ГЛОБАЛЬНИХ ЗМІН - Лопатинський, Юрій; Кіндзерський, Віталій; Остапенко, Станіслав (Чернівецький національний університет імені Юрія Федьковича, 2022)
Досліджено трактування, роль і значення інституцій. Наведені елементи класифікації інституцій. Розглядаються рівні інституцій (міжнародний; національний; регіональний / місцевий; індивідуальний). Подані елементи оцінювання соціальних інституцій. Окреслено інституційні зміни – трансформацію інституцій у транзитивному суспільстві. Внесені пропозиції поліпшення соціальних інституцій в умовах глобальних змін.
INSTITUTIONS UNDER GLOBAL CHANGES
The aim of the research is to outline the directions for improving social institutions in the context of global changes. The article examines the interpretation, role, and significance of institutions. In institutionalism theory, the focus is on the individual as an active member of society. The research presents elements of institutional classification: formal and informal, effective and ineffective. The levels of institutions are discussed: international, national, regional/local, and individual. Global changes in the world economic system are outlined – polycrisis and the factors that determine it. The elements of indirect assessment of the impact of social institutions on the efficiency and performance of the national society are provided: Democracy Index, Economic Freedom Index, Corruption Perception Index, and Global Innovation Index. The level of trust in social institutions in Ukraine is analyzed. One of the main results of the research is to determine the necessity and directions for institutional changes – the transformation of institutions in a transitive society. It is noted that Ukraine currently has a "window of opportunities" to overcome the negative consequences, although there are many challenges. It is emphasized that modernization should be the form of future changes. Proper institutional frameworks are important - the formation of appropriate institutions at the central and local levels, formal and informal. The role of human capital is emphasized, and the driving force of development will be passionate individuals and civil society institutions. The development of a modern national state reveals the dialectic of institutions and individuals, their two-sided connection. Proposals for improving social institutions in the current context of global changes are made.
Keywords: інституції, інституційні зміни, трансформація, глобалізація, полікриза; institutions, institutional changes, transformation, globalization, polycrisis